Intercultural education in educational centres with high cultural difference in Cataluña (España) - Jordi Garreta-Bochaca; Angeles Torrelles-Montanuy (University of Bologna, 2020)
The educational system in Catalonia (Spain) has experienced a notable increase in the number of students of foreign origin, especially from the years 2000 onwards, which has led to the gradual incorporation of greater recognition of cultural diversity in speeches, policies, official documents and practices. Therefore, the study presented here focuses on the schools with a high presence of this student body (defined by more than 50%). Based on an extensive survey of school representatives and an ethnography, the actions that they carry out in the face of growing cultural diversity, what skills they believe students need to interact in it and how they define intercultural education are defined. The results show that students of foreign origin are unevenly distributed in schools and according to ownership (public/private), that there are still doubts as to what should be achieved with intercultural education and that action is taken more generally, in line with school documentation, than specifically.